Community Empowerment in Application of Solar-Powered Automatic Irrigation For Chilli Farming on a Rainfed Rice - Ardiansyah, Heri; Agustina, Rohmatin Farida (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
The low productivity of rainfed lowland rice during the dry season, a critical factor in reduced farmer income and compromised food security, has been effectively addressed by a community team through the introduction of an automatic solar-powered irrigation system. This innovative approach, encompassing group discussions, construction of the irrigation system, and training in chilli cultivation with the new technology, has significantly enhanced crop yield and farmer income. Specifically, the technology has doubled farmers' earnings outside the rainy season, with chilli cultivation yielding 6.75 t/ha and generating IDR46,182,061 in income. The economic viability of this technology is underscored by its positive net present value (NPV) of IDR154,918,858, an internal rate of return (IRR) of 36%—surpassing the 6% discount rate—a profitability index (PI) of 1.99, and a payback period (PP) of 2.5 years. The overwhelming positive response from farmers, with 53% planning to adopt this technology in the upcoming dry season, either individually or in collaboration, highlights its effectiveness in not only boosting income but also in fostering a positive attitude towards innovative cultivation practices in challenging conditions.